2020
DOI: 10.1016/j.bjid.2020.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Brazilian ZIKV strain replication in primary human placental chorionic cells and cervical cells treated with nitazoxanide

Abstract: Zika virus (ZIKV) infection during pregnancy is associated with a congenital syndrome. Although the virus can be detected in human placental tissue and sexual transmission has been verified, it is not clear how the virus reaches the fetus. Despite the emerging severity caused by ZIKV infection, no specific prophylactic and/or therapeutic treatment is available. The aim of the present study was to evaluate the effectiveness antiviral of nitazoxanide (NTZ) in two important congenital trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Interestingly, they were likewise falsely recommended against earlier to manage COVID-19 20 before later proven safe and even lifesaving in SARS CoV-2, RSV, Influenza and Norwalk viral infections through earlier real-life practice and later clinical trials 1,21-23 as early treatment aborts the progression of these viral infection and abolishes the occurrence of the complications in the vast majority of cases, in not all of them 24 . Notably, nitazoxanide and/or its active metabolite; tizoxanide were previously shown to in-vitro inhibit the replication of some flavivirdae including dengue virus serotype 2 25,26 . Moreover, nitazoxanide was also suggested to be effective against paramyxovirus infection including parainfluenza and humanmetapneumovirus 27 .…”
Section: Using Nsaids and Kelleni's Protocol To Early Manage Dengue F...mentioning
confidence: 99%
“…Interestingly, they were likewise falsely recommended against earlier to manage COVID-19 20 before later proven safe and even lifesaving in SARS CoV-2, RSV, Influenza and Norwalk viral infections through earlier real-life practice and later clinical trials 1,21-23 as early treatment aborts the progression of these viral infection and abolishes the occurrence of the complications in the vast majority of cases, in not all of them 24 . Notably, nitazoxanide and/or its active metabolite; tizoxanide were previously shown to in-vitro inhibit the replication of some flavivirdae including dengue virus serotype 2 25,26 . Moreover, nitazoxanide was also suggested to be effective against paramyxovirus infection including parainfluenza and humanmetapneumovirus 27 .…”
Section: Using Nsaids and Kelleni's Protocol To Early Manage Dengue F...mentioning
confidence: 99%
“…Subsequently, Li et al (146) demonstrated that Nitazoxanide inhibited ZIKV infection by decreasing viral replication and viral protein expression in human placental epithelial cells, human neuronal progenitor cells and human pluripotent stem cell line. Thereafter, De Souza et al (142) found that Nitazoxanide reduced ZIKV viral loads up to 2 logs in primary cultured chorionic cells obtained from human term placentas and in a human cervical epithelial cell line. Recently, Guzeloglu-Kayisli et al ( 104) evaluated the anti-ZIKV activity of tizoxanide in primary cultures of HESCs obtained from cycling…”
Section: Potential Therapeutic Options Against Zikv Infectionmentioning
confidence: 99%
“…Notably, nitazoxanide and/or its active metabolite; tizoxanide were previously shown to in-vitro inhibit the replication of some flavivirdae including dengue virus serotype 2 [18,19]. However, until other reports or clinical trials can confirm my recommendation for the early use of ibuprofen/NSAIDs in the management of dengue fever, it is vigilant to prescribe NSAIDs basing on a personalized approach and to prescribe paracetamol together with nitazoxanide to those presenting relatively late while seeking the medical advice and/or lacking urgent medical intervention in their local areas as in the remote impoverished areas, regardless of the results of tourniquet test.…”
mentioning
confidence: 99%